Prototype Design Of Client-Server Architecture And Geo-Bi Tools In Commodity Price Monitoring Based On Public Participation - Fathulloh, Fathulloh; Saraswati, Nurul Mega; Permana, Satria Dendi (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
Commodity price stability is a critical pillar in maintaining regional economic resilience and mitigating inflation. However, conventional data collection methods often face significant operational challenges, including high costs, time lags, and limited personnel. This study proposes an innovative, low-cost digital solution by designing a system prototype that integrates a client-server architecture with Geographic Business Intelligence (Geo-BI) tools based on community participation (crowdsourcing). The proposed model utilizes local village officials as enumerators to transmit price data to a Virtual Private Server (VPS) PostgreSQL database, incorporating automated GPS coordinate tracking to ensure spatial validity. Testing using simulated data demonstrates that an intermittent sampling strategy is architecturally capable of capturing macro price trends without overburdening local human resources. Visualizations through an interactive dashboard effectively facilitate early detection of price and spatial anomalies, thereby contributing to public sector transparency and accountability in supporting good governance.